2021
DOI: 10.3389/fpls.2021.752108
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic Effect of Proton Beams Characterized by Phenotypic Analysis and Whole Genome Sequencing in Arabidopsis

Abstract: Protons may have contributed to the evolution of plants as a major component of cosmic-rays and also have been used for mutagenesis in plants. Although the mutagenic effect of protons has been well-characterized in animals, no comprehensive phenotypic and genomic analyses has been reported in plants. Here, we investigated the phenotypes and whole genome sequences of Arabidopsis M2 lines derived by irradiation with proton beams and gamma-rays, to determine unique characteristics of proton beams in mutagenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 64 publications
2
10
1
Order By: Relevance
“…Similarly, Weng et al (2019) found that spontaneous mutation profile in Arabidopsis do not occur evenly across the genome: they are biased toward G: C to A: T transitions ( Weng et al, 2019 ). Similar results were observed in the gamma rays, carbon-ion beams, LR, and proton beams induced mutations ( Guo et al, 2019 ; Li et al, 2019 ; Xiong et al, 2019 ; Yang et al, 2019 ; Oono et al, 2020 ; Choi et al, 2021 ; Lee et al, 2021 ), which is also consistent with the present study. Therefore, the uneven distribution of IR induced mutations may be related to mutational bias.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, Weng et al (2019) found that spontaneous mutation profile in Arabidopsis do not occur evenly across the genome: they are biased toward G: C to A: T transitions ( Weng et al, 2019 ). Similar results were observed in the gamma rays, carbon-ion beams, LR, and proton beams induced mutations ( Guo et al, 2019 ; Li et al, 2019 ; Xiong et al, 2019 ; Yang et al, 2019 ; Oono et al, 2020 ; Choi et al, 2021 ; Lee et al, 2021 ), which is also consistent with the present study. Therefore, the uneven distribution of IR induced mutations may be related to mutational bias.…”
Section: Discussionsupporting
confidence: 93%
“…In Arabidopsis , mutation rates induced by gamma rays (M 2 –M 6 ) and carbon-ion irradiation (M 2 ) were 1.4–2.2 × 10 –7 and 0.9–1.2 × 10 –7 /bp ( Hase et al, 2020 ). However, the mutation rates obtained in the present study were higher than those estimated by these previous studies ( Li et al, 2019 ; Yang et al, 2019 ; Hase et al, 2020 ; Oono et al, 2020 ; Lee et al, 2021 ). The present study demonstrates that LR and CR radiation are all effective for mutation induction in wheat, suggesting that CR and LR could be good mutagens for plant mutation breeding in the future.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…As a dense IR, it has higher linear energy transfer (LET), which is defined as the energy per unit track length, and it shows a higher relative biological effectiveness in lethality and mutation [ 58 , 90 ]. Based on these, heavy-ion beams show many outstanding advantages, for instance, a lower damage rate, a higher mutation rate, and a wider mutational spectrum, which generate the unique variations which are different from those induced by electromagnetic radiation [ 91 , 92 ]. Further, ROS generated by ionizing the water molecules in cells during heavy-ion beam irradiation show a biphasic dose response, and on the one hand, it activates a variety of positive physiological and metabolic behaviors, such as breaking dormancy, accelerating germination, and enhancing the antioxidant capacity at low doses, while on the other hand, it causes negative oxidative stress and exerts inhibitory effects on organisms at high doses [ 25 , 93 ].…”
Section: Ionizing Physical Priming and Plant Responsesmentioning
confidence: 99%
“…Studies aimed at understanding the molecular effects of the physical mutagens at whole-genome level is increasingly being pursued with the advent of rapid technological developments in the eld of genomics such as the nextgeneration sequencing (NGS). NGS has been used to unravel the molecular effects of spontaneous mutations (Weng et al 2019) as well as those induced by various physical mutagens like gamma-rays (Hase et al 2020), X-rays (Nath et al 2020), ion-beams (Hase et al 2018;Kazama et al 2017), proton beams (Lee et al 2021), andneutrons (Bel eld et al 2012). This coupled with superior bioinformatic algorithms provide a holistic approach in novel understanding of the mutagenic effects of various physical mutagens in different genomic backgrounds.…”
Section: Introductionmentioning
confidence: 99%